Social problems in the age of COVID-19. - Muschert, Glenn W.; Budd, Kristen M.; Christian, Michelle; Lane, David C. (Writer on tattooing); Smith, Jason A., 1984- (Rapid response., 2020)
Written by a team of authors brought together by the Society for the Study of Social Problems (SSSP), this book provides accessible insights into pressing social problems in the United States in the aftermath of the COVID-19 pandemic and proposes public policy responses for victims and justice, precarious populations, employment dilemmas and health and well-being. --